Basilar invagination in Rheumatoid Arthritis – A Silent Crusader (Indian Journal of Case Reports, 2026)
Basilar invagination is a rare complication of cervical spine involvement in rheumatoid arthritis. It occurs in untreated, long standing disease with erosive, deforming arthritis. It can cause medullary compression leading to myelopathy or cranial nerve palsies . It is a neurological emergency that requires urgent surgical intervention to prevent lifelong morbidities. This image highlights importance of adequate disease control, patient compliance and delayed articular complications of untreated rheumatoid arthritis.